Right hand techniques of undergraduate classical guitarists / Saufi Muhammad Athir Asahari - Saufi Muhammad Athir, Asahari (2014)
This study aims to ascertain how aware classical guitar students are concerning the importance of right hand techniques in guitar playing. It identified problems in right hand techniques of undergraduate classical guitarists at the Faculty of Music Universiti Teknologi MARA (UiTM) and located the causes of the problems. This study also help the students to understand about the right hand techniques such as tremolo, arpeggio, and right hand position, and how they apply while practice and playing the classical guitar. This study is also necessary to reduce the weaknesses in mastering the appropriate methods to play the classical guitar. It is because many of them always face the difficulties to apply their right hand techniques while playing classical guitar.